Brazilian migration to Portugal. Social networks and ethnic solidarity - Padilla, Beatriz (2006)
This paper describes the flux of Brazilian newcomers to Portugal. It focuses on the type of interactions and social networks they make use of, in both the country of origin and destiny, in order to find housing and work and build support. It also looks at gender differences in the use of networks, and explores the issue of ethnic solidarity in social relations among Brazilians migrants. This work is based on more than 40 in-depth interviews and ethnographic fieldwork carried out in Lisbon and Mato Grosso do Sul (Brazil).